EKOLOGI SASTRA POLITIK DALAM NOVEL SEBUAH WILAYAH YANG TIDAK ADA DI GOOGLE EARTH KARYA PANDU HAMZAH - Putri Ayu Cahyani (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2022)
With a background in the foothills of Mount Ciremai, Pandu Hamzah (2015) critiques environmental problems in the Ciremai area through his novel, Sebuah Wilayah yang Tidak Ada di Google Earth. This novel describes the phenomenon of political problems in society related to the use of nature. Therefore, the variety of studies that can be used is political ecology. This research is a qualitative descriptive study that aims to thoroughly describe political ecology in Pandu Hamzah's novel Sebuah Wilayah yang Tidak Ada di Google Earth. The results showed that the form of political ecology in the novel A Territory that Doesn't exist in Google Earth is contained in the characteristics, interests, and actions of actors. Characteristics of actors in the Sebuah Wilayah yang Tidak Ada di Google Earth are divided into anthropocentric, biocentric, and ecocentric. The interests of actors in the Sebuah Wilayah yang Tidak Ada di Google Earth that are highlighted come from groups of countries, companies, non-governmental organizations, and grassroots actors. Actor's actions in the Sebuah Wilayah yang Tidak Ada di Google Earth Earth are manifested in the form of an institutionalized and organized environmental movement. Keywords: Political Ecology, Pandu Hamzah, and “Sebuah Wilayah yang Tidak Ada di Google Earth” Novel